Changes in phytoplankton composition hinder the recovery from eutrophication in a perialpine lake (Lake Lugano, Switzerland and Italy). (15th December 2021) - Lepori, Fabio; Capelli, Camilla; Foresti, Danilo
Abstract: We investigated the factors shaping the response of summer phytoplankton biomass to declining phosphorus (P) concentrations in a lake undergoing restoration (South basin of Lake Lugano, Switzerland and Italy). During 1989–2019, summer P concentrations declined from values typical of eutrophic lakes (>30 μg L −1 ) to values typical of mesotrophic lakes (10–30 μg L −1 ). Contrary to expectations, this decline was not followed by a decline in phytoplankton biomass. Instead, phytoplankton biomass showed the highest values in summers with lowest P concentrations. This paradoxical effect was associated with a change in phytoplankton composition. Higher P concentrations were associated with higher relative biomass of green algae, lower P concentrations with higher biomass of cyanobacteria and diatoms. We interpreted this change as a shift from edible and P-demanding phytoplankton to inedible and P-efficient phytoplankton, leading to different trophic structures. The pattern observed may be prompted by the particular conditions of deep lakes approaching mesotrophy, including occurrence of deep-water P reserves and high N concentrations, which can benefit inedible metalimnetic cyanobacteria. To attain reductions in summer phytoplankton biomass, restoration efforts may need to further reduce P concentrations and, possibly, address N enrichment.